Peningkatan Kualitas Calistung melalui Permainan di Sekolah Dasar di Kelurahan Mangli - Ahmad Fadli; Yuli S; Lathifah Cahyani P3; Septianing Tyas K; Abdul Malik K.A; M. Zamroni (LPPM STKIP PGRI Pacitan, 2024)
Literacy is literacy, namely the ability to write and read. In the Mangli sub-district there are several problems found, one of which is in elementary schools where the literacy and numeracy levels of students are still low. The form of service carried out by students in the field of education in the Mangli sub-district is by carrying out the calistung program through interesting learning in the form of word order games and multiplication smart board learning media. Calistung is an acronym for learning to read, write and count. In elementary school education students are required to learn basic things in the world of education, especially reading, writing, and arithmetic. The dedication methodology uses a method based on community empowerment. This program is implemented in 2 schools, namely SDN Mangli 1 and SDN Mangli 4. The aim of this program is to improve students' basic abilities by implementing interesting learning in the form of games so students don't feel bored when they have to receive monotonous lessons. At the time of program implementation, the enthusiasm of the students for the learning concepts that we had compiled was very high. The results of the dedication to implementing this program can run as expected with an increase in the quality of students' calistung abilities in